2022
DOI: 10.3389/fbioe.2022.858656
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels for Treatment of Different Degrees of Osteoarthritis

Abstract: Osteoarthritis (OA) is a common disease that severely restricts human activities and degrades the quality of life. Every year, millions of people worldwide are diagnosed with osteoarthritis, placing a heavy burden on society. Hydrogels, a polymeric material with good biocompatibility and biodegradability, are a novel approach for the treatment of osteoarthritis. In recent years, this approach has been widely studied with the development of materials science and tissue engineering technology. We reviewed the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 121 publications
0
21
0
Order By: Relevance
“…Interestingly, through the amplitude and frequency sweep study, we have revealed that the fabricated hydrogel can also resist the deformation caused by mechanical stress, which is very crucial as, during the RA, circumventing joint pain is necessary. When injected into the joint cavity, this hydrogel swells after absorbing the body fluid and forms a cushion-like scaffold, which minimizes the bone-to-bone contact [ 51 , 52 ]. Furthermore, through several in vitro studies, we have also verified the biodegradability and biocompatibility of the fabricated hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, through the amplitude and frequency sweep study, we have revealed that the fabricated hydrogel can also resist the deformation caused by mechanical stress, which is very crucial as, during the RA, circumventing joint pain is necessary. When injected into the joint cavity, this hydrogel swells after absorbing the body fluid and forms a cushion-like scaffold, which minimizes the bone-to-bone contact [ 51 , 52 ]. Furthermore, through several in vitro studies, we have also verified the biodegradability and biocompatibility of the fabricated hydrogels.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a typical complex and multifactorial joint disease that requires combination therapy as it involves a cascade of pathological processes, beginning with damage to the articular cartilage and leading to a disruption of lubrication. Clinically, over 60% of individuals with OA are in the advanced stage, where chronic joint inflammation, dysfunction in lubrication, and degradation of cartilage tissue are recognized as the three crucial aspects that worsen the condition. , The increasing evidence suggests that a combination of multiple drugs may present a promising strategy for more effective treatment of OA. However, existing treatments primarily concentrate on only partial OA key factors, effectively alleviating the symptoms but failing to recover advanced OA . Addressing the three crucial factors simultaneously and achieving sustained effectiveness are essential to halting the progression of advanced OA, but the rational design of these systems is highly complicated and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches provide a new avenue for research in cartilage regeneration [ 15 ]. There are two frontline trends of hydrogel-based therapies for OA therapy [ 15 , 16 ]. The first one is using a hydrogel-based tissue scaffold implants for cartilage tissue regeneration, which falls within the scope of tissue engineering [ 17 19 ].…”
Section: Introductionmentioning
confidence: 99%